Entrepreneurial learning: peripherality and connectedness. Issue 3 (2nd May 2017) - Rae, David
Abstract : Purpose: The purpose of this paper is to explore the roles of peripherality and centrality in relation to entrepreneurial learning and development. Peripherality has previously been considered from a mainly geographical perspective as being remote, loosely connected and marginal. A broader conception of the topic is addressed, asking: in what ways is peripherality relevant to entrepreneurial learning? How can centre-peripheral connectivity enhance this? What are the implications for communities, learners and educators? Design/methodology/approach: Discourses of entrepreneurship development relating to policy, economics, geography and culture favour the concept of centres, which attract attention, resources, activities and people. Whilst peripherality is an enduring topic of interest in regional studies, it is widened through using the conceptualisation of legitimate peripheral participation in social learning as a methodological lens for the study. A case study of the technology sector in Cape Breton, Canada is included to illustrate peripheral entrepreneurship. Findings: The paper suggests ways in which peripheral-central relationships can be a positive factor in entrepreneurial learning. It suggests that rebalancing the bidirectional "flow" of knowledge, talent and resources between centres and peripheries can enhance the value of peripheral entrepreneurship, learning and innovation. Social implications: The paper connects with prior work on community economic development, offering observations for entrepreneurial learning and development of knowledge-intensive businesses in peripheral areas. Boundary-spanning leadership and skills are required to facilitate peripheral-central interaction and entrepreneurship. Originality/value: Peripherality is defined more widely than in prior work, suggesting peripheral learning is part of the fundamental human experience and offers new insights, innovations and opportunities which can create shared value. A conceptual framework for peripheral-central entrepreneurial learning is proposed, which may assist in rebalancing central-peripheral value creation, innovation and regeneration.